Intelligence in the modern world : John Dewey's philosophy - Dewey, John, 1859-1952; Ratner, Joseph, 1901- (New York : Modern Library, 1939)
Selections from writings of John Dewey, with a 241 p. introduction by the editor
Science And Philosophy Of Education : Education as a Science ; Sources of a Science of Education ; Traditional vs. Progressive Education ; Philosophy of Experience ; The Organization of Study ; Means and End of Education -- The Schools And The Social Welfare : The Schools in the Social Order ; Education and Social Change ; Educators and the Class Struggle ; The Schools and Religions ; Democracy in the Schools ; Academic Freedom ; Education and American Culture -- The Psychology Of Conduct : Habits and Will ; Impulses and Instincts ; Intelligence -- Intelligence In Morals : Individual and Social Morality ; Reflection in the Moral Situation ; Experimentalism in Moral Theory ; Endings in Nature and Ends for Man ; The Satisfying and the Valuable -- Perception, Language and Mind : Theory of Perception ; Physical, Psychophysical and Mental ; Language and Mind ; Mind and Consciousness ; The Unity of the Human Being -- Thinking And Meaning : The Natural History of Thinking ; The Pattern of Reflective Thinking ; The Development of Meanings ; Systems of Meanings and Symbols -- Principles Of Logic : The Genesis of Logical Forms ; Explanation of Situation ; Judgment and Proposition ; Interpretation of the Syllogism ; Induction and Deduction -- Knowledge, Science And Truth : Meanings: Valid and Invalid ; Knowledge as Instrumental and Hypothetical ; Experimental Verification and Truth ; Pure and Applied Science ; Social Science and Social Control -- The Artistic-Esthetic In Experience : The Roots of Esthetic Experience ; The Experience of Esthetic Quality ; The Work of Art and Esthetic Perception ; Substance and Form ; Art, Philosophy and Morals -- The Religious In Experience -- Comprehensive Working Ideas : Continuities in Nature ; The Methods of Philosophy ; Precarious and Stable Events ; Process and Structure ; Causes and Effects (Means and Ends) ; The Social
Supplemented by: A critical index, indexing all Dewey's ideas and explications of terms ... Also a supplementary analytic index ... (28, 8 l ; 29 cm.) published: Sharon, Mass. : Edward A. Post, 1960. Call no.: B945.D41 R17 Index
Includes bibliographical references and indexes
Keywords: Dewey, John, -- 1859-1952; Intellect; Intelligence; Dewey, John, 1859-; Dummies (Publishing)